2020
DOI: 10.31744/einstein_journal/2020rc4990
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial radioembolization for liver tumors as neoadjuvant therapy: three case reports

Abstract: Transarterial radioembolization (TARE) with yttrium-90 microspheres is a palliative locoregional treatment, minimally invasive for liver tumors. The neoadjuvant aim of this treatment is still controversial, however, selected cases with lesions initially considered unresectable have been enframed as candidates for curative therapy after hepatic transarterial radioembolization. We report three cases in which the hepatic transarterial radioembolization was used as neoadjuvant therapy in an effective way, allowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…With the development of glass and resin Y90 microspheres in the 1990s, several studies demonstrated its potential role for advanced-stage hepatocellular carcinoma [16]. Nowadays, its applications have evolved for several types of malignancies and for different situations in the treatment pathway for patients with cancer, not more restricted to the salvage setting for patients with chemorefractory disease [11,12,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the development of glass and resin Y90 microspheres in the 1990s, several studies demonstrated its potential role for advanced-stage hepatocellular carcinoma [16]. Nowadays, its applications have evolved for several types of malignancies and for different situations in the treatment pathway for patients with cancer, not more restricted to the salvage setting for patients with chemorefractory disease [11,12,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The commercial dosimetry software, MIM SurePlan LiverY90 ® (MIM Software Inc., Cleveland, OH) was used for absorbed dose calculation [ 10 , 11 , 15 ]. The tumors received 199 and 70 Gy at V70 (V70 = mean tumor dose to top 70% of tumor volume), respectively.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is a costly treatment and is not widely available. Although SIRT is considered a palliative treatment, there have been reports of patients in whom HCC was downstaged after SIRT and who subsequently underwent tumor resection, liver transplantation, or both, thus being given the possibility of a cure ( 10 ) .…”
mentioning
confidence: 99%